Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2010
DOI: 10.1145/1646353.1646392
|View full text |Cite
|
Sign up to set email alerts
|

Managing a corporate open source software asset

Abstract: Introduction We define corporate open source (COS) as applying the precepts and methodologies prevalent in the open source development community for creating industrial-strength software projects in a corporation for internal use. It may seem that open source style development - using informal processes, voluntary assignment to tasks, and having few financial incentives - may not be a good match for commercial environments. Our ongoing work, however, de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
53
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(53 citation statements)
references
References 6 publications
0
53
0
Order By: Relevance
“…Gurbani et al [24] describe two different models to implement an Inner Source program: infrastructure-based and project-based. We discuss both models below.…”
Section: Inner Source Modelsmentioning
confidence: 99%
See 4 more Smart Citations
“…Gurbani et al [24] describe two different models to implement an Inner Source program: infrastructure-based and project-based. We discuss both models below.…”
Section: Inner Source Modelsmentioning
confidence: 99%
“…In the project-based Inner Source model, there is one division (called the ''core team'') within the organization funded by other divisions that take over the responsibility of a critical resource (shared asset) and makes it available to the other divisions as a shared asset [24]. Gurbani et al have reported on a project-based Inner Source model applied at Alcatel-Lucent [5,24], where the shared asset was a telecommunications signaling server used in a Software Product Line (SPL) [26].…”
Section: Project-based Inner Source Modelmentioning
confidence: 99%
See 3 more Smart Citations